Pengaruh Media Film Bilal: A New Breed Of Hero Pada Nilai Tauhid Di SMPI Al Maarif 01 Singosari Malang - Ahmad Sayyidiman Hamidalloh (Universitas Hamzanwadi, 2025)
This research aims to assess the influence of film media as a learning tool in enhancing the understanding of the value of monotheism among junior high school students. The film Bilal: A New Breed of Hero was chosen as the medium because it contains strong spiritual messages. The method used is an experiment with a quantitative approach. The research subjects consist of two groups: the experimental group that received learning through film media, and the control group that used conventional methods. The analysis results indicate that the use of film as a learning medium has a significant impact on enhancing students' understanding of the value of monotheism. Thus, film media can be an effective alternative in the education of religious values.